Weeds Infestation and Survivability of Mulberry Cuttings in Nursery - Singh, Amardev; Bhatia, N. K.; Chouhan, Sahadev (Indian Forester, 2023)
An experiment was conducted at Silkworm Seed Production Centre (SSPC), Udhampur J&K, UT during 2020-21 to assess the survivability of two different mulberry varieties and kinds of weeds infestation in mulberry nurseries and placed them under respective families. During the present studies, it was found that two weeds infestation were predominant in the mulberry nursery viz., Cynodon dactylon L. and Parthenium hysterophrus L.. Further, the comparative mean data showed highest length of the saplings in S-1635 (1.765 m) and the numbers of cuttings survived was also found highest in the S-1635 saplings.